Food security and forest access in the Colombian and Peruvian Amazon: How do forest quality and belonging to an ethnic group play a role? - Buritica, Alexander; Vanegas, Martha; Pierce, Deborah; Quintero, Marcela (2024)
Food security is vital for a decent life, particularly in early development and with lasting adult health effects. Forests have historically played a key role by offering essential ecosystem services and a direct source of diverse, nutrient-rich foods and medicines. This study explores the link between forests and food security in Colombian and Peruvian Amazon communities. Panel data from households in each country was collected to calculate a multidimensional household-level food security index. Our findings reveal that households with forest access have higher food security, however the effect of this depended on the quality of the forest. Indigenous communities in Colombia also relied more on the forest than non-Indigenous communities in Peru. These findings suggest that the impact of forests on food security depends on the quality of the forest, the cultural practices of those accessing the forest, and the proximity and ease of accessing the forest.